Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.474
|View full text |Cite
|
Sign up to set email alerts
|

Putting a Price Tag on Personal Information - A Literature Review

Abstract: In the digital age, personal information is claimed to be the new commodity with a rising market demand and profitability for businesses. Simultaneously, people are becoming aware of the value of their personal information while being concerned about their privacy. This increases the demand of direct compensation or protection. In response to the commodification of privacy and the increased demand for compensation, a number of scholars have shed light on the value people assign to their personal information. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…In line with some previous research (Wagner et al 2018) and in contrast to other studies (Grossklags and Acquisti 2007), our findings show that individuals state positive willingness to pay to ensure their personal data remains private, at least for some types of data. We observed a surprising degree of consistency in participants' rankings of different data types elicited through different techniques, which indicates that stated preference evaluation techniques may be appropriate tools to reveal individuals' underlying preferences for privacy.…”
Section: Privacy Preferencessupporting
confidence: 91%
See 1 more Smart Citation
“…In line with some previous research (Wagner et al 2018) and in contrast to other studies (Grossklags and Acquisti 2007), our findings show that individuals state positive willingness to pay to ensure their personal data remains private, at least for some types of data. We observed a surprising degree of consistency in participants' rankings of different data types elicited through different techniques, which indicates that stated preference evaluation techniques may be appropriate tools to reveal individuals' underlying preferences for privacy.…”
Section: Privacy Preferencessupporting
confidence: 91%
“…Since these early investigations, there has been ongoing interest in attempting to value the protection of privacy online. A systematic review of the literature regarding "putting a price tag on personal information" was conducted by Wagner et al (2018). They found that the type of information being disclosed (or protected) was an important feature in determining the amount that individuals were willing to pay (or accept).…”
Section: Literaturementioning
confidence: 99%
“…They responded using another open-ended text field. Following this question, we asked participants to answer several Likert-scale questions using the following 5-point scale:"Definitely A (1)," "Likely A (2)," "Equally A and B (3)," "Likely B (4)," and "Definitely B (5)." with respect to specific privacy and securityrelated practices.…”
Section: Consumer Expectationsmentioning
confidence: 99%
“…Potentially misleading representations may run afoul of the FTC's prohibitions against deceptive practices and state laws prohibiting unfair business practices, as well as general privacy regulations, such as the GDPR and CCPA. Finally, such inquiry can also inform economic models exploring the viability of "pay for privacy" consumer protection models [2].…”
Section: Introductionmentioning
confidence: 99%
“…• In Putting a Price Tag on Personal Information -A Literature Review, Amina Wagner et al [13] provide an overview of the literature on the value people assign to their personal information and how to deal with possible direct compensation or protection.…”
Section: Introductionmentioning
confidence: 99%